(untitled) (Pedagogy of Higher and Secondary Education, 2014)
Serduk T. V. Negative factors applying group forms of teaching and learning of students. The author is analysing negative factors which can accompany the use of group forms of organization of educational-cognitive activity in an educational process, she is offering the possible ways of it warning or overcoming.